TECHNOLOGY OF DIFFERENTIATED APPROACH IN THE FORMATION OF COGNITIVE-SPEECH KNOWLEDGE AND SKILLS IN STUDENTS WITH HEARING IMPAIRMENTS (Academia Science Repository, 2023)
At present, in special education, along with traditional teaching methods, the use of interactive approach technologies in the formation of cognitive-speech knowledge and skills in students with hearing impairments is spreading. In this article, we propose as a technology for an interactive approach in the formation of cognitive-speech knowledge and skills in students with hearing impairments to organize lessons using visual communication tools, that is, video content, through which you can expand learning opportunities.